Crypto-Agile Ethereum Transactions: A Hybrid Post-Quantum Architecture for Besu - Dantas, J. B. S.; Silveira, E. M.; Fontes, R.; Cruz, A.; Santos, A. F. P. dos; Bragança, J. F.; Moraes, D. H.; Fava, R.; Rosendo, L.; Petry, J.; Oliveira, M. C. de; Fanchini, F. F.; et al. (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2026: Anais do XXVI Simpósio Brasileiro de Cibersegurança, 2026)
Quantum computing represents a critical threat to classical ECDSA-based blockchains. This paper introduces a crypto-agile framework natively integrated into Besu, proposing novel transaction types that support hybrid post-quantum signatures (e.g., ECDSA-MLDSA44 using the Strong Nesting combiner) while addressing the lack of public key recovery. Evaluated under QBFT consensus, the results show that while local transaction pool ingestion remains performant, the cumulative overhead of validating large cryptographic payloads significantly delays block finalization and degrades global network throughput. This demonstrates that the primary bottleneck for post-quantum migration lies within the consensus layer rather than local transaction routing, offering key insights for future ledger optimization.